Compositional aspect-oriented design pattern properties - Vaira , Žilvinas; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2009)
In this publication we analyze traditional object-oriented design pattern aspectual compositions implemented in object-oriented framework. The main task is to look whether the design pattern compositions present concern duplications, and if they do then what causes it and how to avoid it.
Keywords: aspect-oriented programming; design patterns; design pattern composition